Sosialisasi Peran Gender dalam Pelaksanaan Peraturan Daerah Ketapang Nomor 3 Tahun 2023 - Rangga, Boy; Zulkarnain, Zulkarnain; Fadilah, Nurul; Putri Ira, Nurmaya; Rochman, Auliya; Widya Ningrum Palureng, Rurika; Ayu Catherine, Liany (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2024)
In order to increase public awareness of the significance of gender equality in regional development, gender roles were socialized during the implementation of Regional Regulation (Perda) No. 3 of 2023 about Regional Taxes and Retributions in Ketapang Regency. 50 individuals from a range of educational and gender backgrounds participated in this activity, which was held in Sukaharja Village, Delta Pawan District, Ketapang Regency. Lectures, interactive discussions, and simulations were among the techniques employed to inform participants about the regulation's contents and the idea of gender roles. The findings showed that there is still a lack of public awareness of gender equality and regulations, especially with regard to tax and retribution obligations, which are frequently thought of as men's responsibilities. Factors such as limited socialization, low education levels, and patriarchal culture were identified as main barriers. The main conclusion of this activity is the need for more intensive and continuous socialization, the development of easily understandable materials, and improved public services to encourage active community participation in regional development. Recommendations include collaboration with relevant stakeholders, gender-disaggregated data collection, and strengthening the government's role in mainstreaming gender in all stages of development.